Pendidikan Karakter dalam Tafsir Al-Ibriz Karya Bisri Mustofa - Maulida, Fahma; Faridatur Rohmah (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This research is motivated by Bisri Mustofa's statement in tafsir al-Ibriz that one's faith and character must always go hand in hand. The focus of this study will discuss character education in QS. Luqman from the perspective of tafsir al-Ibriz. This research is a qualitative-descriptive research and is a type of library research. Based on the research results, the concept of character education in children in QS. Luqman [31] according to Bisri Mustofa in accordance with Javanese cultural values is that a child must be able to be a good child by (a) being grateful, (b) having faith, (c) being devoted to both parents, (d) doing good, (e) establishing prayer, (f) prohibition of arrogance, (g) being simple in speech and walking. Keywords: Character Education; Tafsir Al-Ibriz; Bisri Mustofa